Establishing children's library in a mall and non-mall setting a case study of the Children's library and Museo Pambata Resource Center - Taruc, Leira Leonor S. (School of Library and Information Studies, University of the Philippines Diliman, 2001)
A full-scale study between two children's libraries in a mall and non-mall setting was undertaken, one is The Children's Library at the Robinsons Galleria mall in Quezon City and the other is the Museo Pambata Resource Center in Manila. Various aspects of two libraries (i. e. staff, facilities, collection, and activities for children and demographic characteristics for children) were examined for comparison.